1974
DOI: 10.1111/j.1464-410x.1974.tb03856.x
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Suppression in the Treatment of Carcinoma of the Prostate

Abstract: Summary Experience of 26 patients with carcinoma of the prostate treated by adrenal suppression with aminoglutethimide is reviewed. 60% of hormone resistant tumours showed some response. A fall in plasma testosterone beyond that achieved by oestrogens was not observed. A high incidence of side‐effects was noted. A limited role for aminoglutethimide in the management of prostatic carcinoma is suggested. Our thanks are due to the Consultant Surgeons, St Peter's Hospitals who referred their cases to us for invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1
1

Year Published

1976
1976
1993
1993

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 14 publications
1
17
1
1
Order By: Relevance
“…Aminoglutethimide is an inhibitor of several enzymes involved in adrenal steroid synthesis (Dexter et al, 1967) and in prostaglandin metabolism (Harris et al, 1983c). The combination of aminoglutethimide and hydrocortisone had previously been reported both to reduce circulating levels of adrenal androgen and, in small numbers of patients, to induce responses in hormone-relapsed advanced prostatic cancer (Robinson et al, 1974;Sanford et al, 1976).…”
mentioning
confidence: 99%
“…Aminoglutethimide is an inhibitor of several enzymes involved in adrenal steroid synthesis (Dexter et al, 1967) and in prostaglandin metabolism (Harris et al, 1983c). The combination of aminoglutethimide and hydrocortisone had previously been reported both to reduce circulating levels of adrenal androgen and, in small numbers of patients, to induce responses in hormone-relapsed advanced prostatic cancer (Robinson et al, 1974;Sanford et al, 1976).…”
mentioning
confidence: 99%
“…Moreover, after adrenal androgen suppression with aminoglutethimide in patients who had become refractory to orchiectomy and exogenous estrogens, a favorable response was observed in three of seven patients [28]. In a similar study, Robinson and coworkers found palliation in 50% of patients [29].…”
Section: Clinical Evidence That Androgen-hypersensitive Tumors Remainmentioning
confidence: 58%
“…There are several reports of AG + HC achieving both objective (Worgul et al, 1983;Drago et al, 1984;Murray & Pitt, 1984) and subjective (Robinson et al, 1974;Rostom et al, 1982;Ponder et al, 1984) responses in advanced prostatic cancer after relapse from first line therapy (orchiectomy or oestrogen therapy). In addition, we (Ponder et al, 1984) and others (Worgul et al, 1983) have demonstrated that this regimen results in reduced plasma androgen levels as it does in postmenopausal breast cancer patients (Samojlik et al, 1980;Harris et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…The demonstration that aminoglutethimide (AG) inhibited the conversion of cholesterol to pregnenolone (Dexter et al, 1967) led to the use of the drug in combination with hydrocortisone (HC) as a so-called 'medical adrenalectomy' in postmenopausal breast cancer patients (Santen et al, 1974) and also with some apparent benefit in prostate cancer patients (Robinson et al, 1974). The mechanism of action of this combination in prostatic cancer has been questioned, since HC is itself an adrenal suppressant and AG is now accepted as acting by aromatase inhibition in breast cancer patients (Santen et al, 1978;Stuart-Harris et al, 1984).…”
mentioning
confidence: 99%